الاستجابة الإكتئابية لدى الأطفال مرضى سرطان الدم في حالة إستشفاء (دراسة ميدانية بمستشفى طب الأطفال القديسة تريزا عنابة) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
ملخص:تهدف الدراسة الحالية إلى التعرف على الاستجابة الاكتئابية لدى الأطفال مرضى سرطان الدم في حالة استشفاء بمستشفى طب الأطفال القديسة تريزا عنابة، ولتحقيق أهداف الدراسة اعتمدت الباحثة على المنهج الإكلينيكي، والمقابلة ومقياس متعدد الأوجه لاكتئاب الأطفال MDC-I بعد أن تمت عملية تكييف المقياس والتحقق من صدقه وثباته كأدوات لجمع البيانات، وتكونت عينة البحث من 09 أطفال مصابين بمرض سرطان الدم وفي حالة استشفاء من الجنسين ذكورا وإناثا. توصلت النتائج إلى أن كل أفراد العينة يعانون من اكتئاب راجع للمرض والوضع الاستشفائي، كما بينت الدراسة بأن مستويات الاكتئاب تختلف لدى أفراد العينة حسب الشدة حيث تراوحت بين المتوسط والحاد والخطير، وحسب الجنس فكل إناث عينة الدراسة كان الاكتئاب لديهم حاد غير أن الذكور تراوحت مستويات الاكتئاب لديهم بين المتوسط والخطير.كلمات دالة: الاستجابة الاكتئابية، سرطان الدم، الاستشفاء، طفولة متأخرة.   Abstract : The current study aims to identify the depressive response in children with leukemia in hospitalization in Saint Teresa Annaba Pediatric Hospital, and to achieve the objectives of the study, the researcher relied on the clinical approach, and on the interview, a multifaceted measure of child depression MDC-I after it was adapted and verified its validity and stability. As tools to collect data, the sample consisted of 09 children with leukemia and in hospitalization of both sexes, males and females, and the results concluded that all members of the sample suffer from depression due to disease and hospitalization, and the study also showed that levels of depression differ among the sample members, as it ranged between The study showed that the level of depression differs according to gender. All the females in the study sample had severe depression, but the males have levels of depression ranged between moderate and severe.Key words: Depressive response, leukemia, hospitalization, children.